Mechanisms of asthma development in elite athletes - Carlsen, K. H. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Asthma is often found in endurance athletes with epithelial damage reported as first step in asthma development (1-3). Airways inflammation increases after a competitive season (4) contributing to BHR of endurance athletes (5). Athletes are exposed to environmental pollution during performance (6). Increased parasympathetic tone is observed in endurance athletes (7), with the following hypothesis of athlete`s asthma proposed (8): With daily training and frequent competitions with increased ventilation, damage occurs to the respiratory epithelium, probably as first step in asthma development. Due to daily training sessions with increased ventilation, healing is delayed. Inflammation, neutrophilic or eosinophilic, dependent upon atopic phenotype occurs with BHR and airway symptoms. Also, endurance training increases parasympathetic activity and bronchial tone, contributing to increased BHR. Also, some sports are performed in environments with exposures as cold air inhaled by winter athletes, organic chlorine compounds in swimming pools, ultrafine particles in ice and traffic air pollution for cyclists. Thus many stimuli contribute to increased BHR, increased airways inflammation and bronchoconstrictor tone. Thus BHR and asthma symptoms may occur, measured objectively by bronchial responsiveness, such as metacholine bronchial challenge or tests for exercise induced asthma.